2008
DOI: 10.1177/0146167208316688
|View full text |Cite
|
Sign up to set email alerts
|

On Being Eager and Uninhibited: Narcissism and Approach–Avoidance Motivation

Abstract: This article demonstrates the validity and utility of conceptualizing narcissistic personality in terms of relative approach-avoidance motivation. Across three studies (N = 1,319), narcissism predicted high approach and low avoidance motivation. That is, narcissists reported being strongly motivated to approach desirable outcomes but only weakly motivated to avoid negative outcomes. Relative approach-avoidance motivation was shown to be useful in terms of explaining behavioral tendencies associated with narcis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
2
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(169 citation statements)
references
References 60 publications
(102 reference statements)
10
151
2
6
Order By: Relevance
“…Vulnerable narcissism has similar features, but is additionally characterized by neuroticism, such as anxiety and low self-esteem (Gore and Widiger 2016;Miller et al 2011). In terms of motivation, grandiose narcissism is driven by more approach-motivation, while the vulnerable type more by avoidance-motivation (Foster and Trimm 2008). Studies report varying relationships between the two forms of narcissism suggesting the trait Neuroticism (the disposition for anxiety) as the key dividing factor (Miller et al 2011).…”
Section: Dark Triadmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulnerable narcissism has similar features, but is additionally characterized by neuroticism, such as anxiety and low self-esteem (Gore and Widiger 2016;Miller et al 2011). In terms of motivation, grandiose narcissism is driven by more approach-motivation, while the vulnerable type more by avoidance-motivation (Foster and Trimm 2008). Studies report varying relationships between the two forms of narcissism suggesting the trait Neuroticism (the disposition for anxiety) as the key dividing factor (Miller et al 2011).…”
Section: Dark Triadmentioning
confidence: 99%
“…Speculatively, the main reason for the differences between the two forms of narcissism (vulnerable vs grandiose) in relation to stress may simply be due to differences in levels of underlying neuroticism -Vulnerable narcissism contains much neuroticism, while grandiose even the opposite which can be thought of as resilience (see Miller et al 2011). The drives behind these can be understood through the lens of Reinforcement Theory, and particularly avoidancemotivation (BIS; Foster and Trimm 2008;Jonason and Jackson 2016). Vulnerable narcissists, sometimes called hyper-sensitive, have a higher avoidance-motivation, while grandiose narcissists have a higher approach-motivation, thus translating into differing stress-levels in the present study.…”
Section: Malevolent Personality and Stressmentioning
confidence: 99%
“…NPI narcissists tend to be extraverted (e.g., Raskin & Hall, 1981) and sensation-seeking (e.g., Emmons, 1981), and NPI scores are consistently positively correlated with measures of approach-focused motivational orientation and often negatively correlated with avoidance-focused motives (Foster & Trimm, 2008;Miller et al, 2009). As Campbell, Goodie, andFoster (2004) put it, NPI narcissists "swing for the fences" in their quest for self-enhancement.…”
Section: Competing Explanations For Narcissistic Self-enhancementmentioning
confidence: 99%
“…Studies have found that those who score high on narcissism do not have the behavioral inhibition that is necessary for long-term goal attainment (Vazire & Funder, 2006). This may be attributable to inaccurate risk taking assessments that emphasize overconfidence for immediate rewards Foster & Trimm, 2008), as well as high sensation-seeking tendencies and high BAS/low BIS motivational systems (Miller et al, 2009). Interestingly, this association became positive after controlling for the shared variance among the traits, suggesting that narcissism in and of itself is associated with the ability to sacrifice immediate rewards in order to obtain future rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathic impulsivity is attributable to poor impulse control (Jones & Paulhus, 2011b), whereas narcissistic impulsivity is related to overconfidence and unrealistic optimism (Paulhus, Harms, Bruce, & Lysy, 2003) and unrelated to limited self-control (Jonason & Tost, 2010). Narcissism is associated with strong approach and weak avoidance motivations (Foster & Trimm, 2008), sensation-seeking tendencies (Emmons, 1981), as well as cognitive biases in risk taking assessment (Foster, Shenesey, & Goff, 2009). As such, narcissistic individuals engage in self-destructive behaviors with little concern for others (Vazire & Funder, 2006), such as gambling (Jones, 2013) and financial risk-taking (Foster, Reidy, Misra, & Goff, 2011).…”
Section: Narcissismmentioning
confidence: 99%